Intersecting Identities: A Critical Examination of Sixsmith’s Ayesha’s Gift - Muhammad Raies; Kiran Jamil; Rashid Ali; Usman Ullah (Social Science Review Archives, 2025)
This study explores the struggles of Ayesha, the protagonist, as she seeks the truth behind her father’s death, officially declared a suicide. Guided by Kimberlé Crenshaw’s theory of Intersectionality (1989), the research examines how overlapping identities—race, ethnicity, nationality, gender, class, and cultural background—shape her experiences. Employing a qualitative, text-based approach, the study reveals Ayesha’s confrontation with systemic oppression and patriarchal dominance in Pakistan, where her intrusion is met with hostility, threats, and violence. Simultaneously, her life in Britain, marked by alienation and racial prejudice, intensifies her sense of displacement. Ultimately, both nations fail to offer her belonging, forcing her into a crisis of identity. This analysis highlights how intersectional forces amplify marginalization and complicate questions of home and identity for diasporic women.